Estimativa da evaporação e evapotranspiração no Baixo São Francisco com uso de modelo FAO e sensoriamento remoto - Santos, Tatiana Vanessa dos (2019)
One of the most important factors in any water management program is having knowledge about the natural processes that regulate the water cycle, with their spatial and temporal dynamics, especially when it comes to spatial and temporal analyzes of these processes. The aim of this study was to estimate evaporation and evapotranspiration in Lower San Francisco, using model from Food and Agriculture Organization (FAO) and remote sensing, from 2009 to 2018. The methodology used to perform this work initially scored in filling data gaps. using the Predictive Mean Matching-PMM method. After validation of the method, it was possible to estimate Evaporation (E) by the Penman method (1948) and Reference Evapotranspiration (ETo) by the PM-FAO method. In detriment of the statistical analyzes performed, the r and REQM values of the stations showed that the filling method was effective and generated reliable values, leading to the acceptance of its results, thus complementing the failures in the series. It can be considered the descriptive statistics performed for the estimated data, where in general the E and ETo in the study region presented a low dispersion of the data in relation to the average, indicating that this parameter (the average) is a good estimator for representation. Another meteorological parameter used in the work was the product ETr (Evapotranspiration Real) obtained through from LSA-SAF, for comparison with surface data, although it had high dispersion for all locations. After statistical proof, it was found from the results that the temporal dynamics of Evaporation were very similar to that of evapotranspiration in most BSF study sites, with only different values at their maximum and minimum values. For annual mean values for the study period, the (E), (ETo) and (ETr) had their highest mean values respectively of 1482.66, 1711.2 and 774.0 mm / year for Brejo Grande (SE), Pão de Açúcar (AL) and Propriá (SE). The lowest values, respectively, were 1264.2, 152.6 and 225.9 mm / year for Traipú (AL), Arapiraca (AL) and Pão de Açúcar (AL). From these results, it was found that the ETr obtained low values, but compared to studies in other physiographically similar regions showed similar results. Further studies are needed to prove this product in semiarid regions for validation in our region. However, the work obtained good results for the other parameters, compared to other studies already carried out in the São Francisco Watershed.